Effect of doping particles on the wear behavior of tungsten materials at varying temperatures - C.S. Ding; X.F. Xie; J.F. Yang; R. Liu; X.B. Wu; X.P. Wang; Z.M. Xie (Journal of Materials Research and Technology)
In the present work, the impact of second-phase particles on the friction and wear properties of tungsten (W) materials across various temperatures was thoroughly examined through detailed morphology characterization and elemental analysis. The results demonstrate that the addition of particles reduces the temperature at which severe adhesive wear occurs while also lowering the wear rate at medium temperatures (200 °C–400 °C). Furthermore, the doped particles alter the friction mechanism of W at high temperatures (>400 °C), where oxide layer lubrication typically dominates. However, in particle-doped W alloys, these particles are prone to detachment due to interactions with the thick, loose oxide layer. This detachment disrupts the lubrication effect, resulting in increased friction and substantial mass loss. Overall, this study offers a comprehensive understanding of the effect of doping particles on the wear performance of W alloys, and offers theoretical guidance for the design of highly wear-resistant W materials.